Character Education in Primary Education with the Ethnopedagogical Approach: Exploring the Meaning and Structure of Culture, Beliefs, and Traditions in Madura Society - Rarasaning Satianingsih; Sunu Catur Budiyono; Subandowo Subandowo; Reza Rahmatullah; Sri Erlinda (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
It is very important to transform cultural values in society so that they are known, accepted and lived up to by the community. The philosophy of Parennialism views the past as a chain of human life that cannot be ignored. The past is an important part of human time travel and has a strong influence on present and future events, therefore the values of the past are valuable must be passed on to today's young generation. Based on the explanation above shows the importance of value education in society. The potential that must be developed in this educational process is the values in local wisdom, especially in the formation of social integration in a society. Character education in primary education with an ethnopedagogical approach through a culture of education based on local wisdom of the Madurese ethnic can function as development: developing the potential of students to become good behavior for students who have attitudes and behaviors that reflect the culture and character of the nation. Improvement: strengthening the work of national education to be responsible for developing the potential of students who are more dignified. Filter: to filter the cultures of one's own nation and the cultures of other nations that are not in accordance with cultural values and national character.